Pembuatan Studio Mini Sebagai Sarana Branding Product di Era Digital Marketing Pada UMKM Keputih Surabaya - Khoirotunnisa, Fani; Wikartika, Ira; Sibarani, Steven Arrow Rinel; Sari, Rafika (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Along with the continued development of digital marketing in product marketing today, it is very necessary to be able to improve product branding for Small, Medium, and Micro Enterprises (MSMEs), especially in Keputih Village, Surabaya. The lack of maximum ability in branding the products offered is due to limited facilities in taking good product photos. Product photos can be used as a visual communication medium, because a good product photo can convey the intent of the photo, so as to increase product knowledge. Making a mini studio as a solution to the problem of the availability of facilities to be used as a studio. The implementation of this mini studio creation activity was carried out in mutual cooperation in Keputih Village with simple tools and materials through the KKNT MBKM UPN "Veteran" East Java activity. This activity can be a solution to the problem of photo studio availability and simplify the process of taking pictures through the use of a mini studio. As a result of this activity, participants and readers of the publications can find out what tools and materials need to be prepared and the costs to be incurred in making a mini studio and the stages in making a mini studio. The mini studio that resulted from this activity was handed over to the Harmoni Keputih Tourism Market to be used by MSME actors and the mini studio module which is expected to be useful for UMKM actors in Keputih.